2007
DOI: 10.1158/1055-9965.epi-07-0084
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect Modification between Estrogen Metabolism Genotypes and Combined Hormone Replacement Therapy in Postmenopausal Breast Cancer Risk

Abstract: IntroductionPostmenopausal use of combined hormone replacement therapy (CHRT) containing both estrogens and progestins has been associated with increased breast cancer risk (1, 2). There is also evidence that genetic variants in candidate estrogen metabolism genes influence the disposition of exogenous estrogen. The genes involved in the disposition of estrogen are well known, and include catechol-O -methyltransferase (COMT), the sulfotransferases SULT1A1 and SULT1E1, and members of the cytochrome P50 family i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
2
12
0
1
Order By: Relevance
“…Consistent with this, we observed that the increased risk of breast cancer associated with years of E+P use was greater among women with at least one rare allele of the CYP1A1 Ile 462 Val and CYP1A1 Msp I polymorphisms. To date, only one other study has evaluated interactions between SNPs in genes involved in hormone metabolism and years of E+P use in the development of breast cancer (31). Rebbeck et al (31) observed no statistically significant modification of the effect of E+P use on breast cancer risk by any of the polymorphisms that they studied; they evaluated CYP1A1 Ile 462 Val but not CYP1A1 Msp I.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we observed that the increased risk of breast cancer associated with years of E+P use was greater among women with at least one rare allele of the CYP1A1 Ile 462 Val and CYP1A1 Msp I polymorphisms. To date, only one other study has evaluated interactions between SNPs in genes involved in hormone metabolism and years of E+P use in the development of breast cancer (31). Rebbeck et al (31) observed no statistically significant modification of the effect of E+P use on breast cancer risk by any of the polymorphisms that they studied; they evaluated CYP1A1 Ile 462 Val but not CYP1A1 Msp I.…”
Section: Discussionmentioning
confidence: 99%
“…Simulated data were generated for eight genes to reflect the empirical dataset described below [30], [31], [32] (Figure 2). Dataset D1 had no factors that confer risk of being a case vs. a control.…”
Section: Resultsmentioning
confidence: 99%
“…These simulated data were intended to reflect frequently encountered empirical allele and genotype frequencies, including unknown (missing) genotypes. Specifically, we generated these simulated data to reflect the data observed in the WISE study [30], [31], [32]. For each dataset, 500,000 individuals were generated to model a variety of genetic risk scenarios involving one or more genotypes conferring an enhanced risk of disease.…”
Section: Methodsmentioning
confidence: 99%
“…SULT1A1 catalyzes the sulfate conjugation of small phenols, such as neurotransmitters and steroid hormones, and rs1801030 defines the SULT1A1*3 allozyme with a p.M223V change (c.A667G) [26]. The *3 variant has a similar or lower intrinsic enzyme activity compared to both the *1 and *2 variant, depending on the substrate [27]. The enzyme activity with regard to serotonin, dopamine, or (nor) adrenaline has not been investigated yet, though one can assume a normal-activity allozyme that has no effect on the catabolism on the before-mentioned neurotransmitters [28].…”
Section: Discussionmentioning
confidence: 99%